2016
DOI: 10.1111/obr.12383
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial environment: definitions, measures and associations with weight status – a systematic review

Abstract: SummarySocio-ecological models suggest that many elements of the social environment act as upstream determinants of obesity. This systematic review examined definitions, measures and strength of associations between the psychosocial environment and adult weight status. Studies were included if they were conducted on adults, the outcome was weight status, carried out in any developed country and investigated at least one psychosocial environmental construct. Six databases for primary studies were searched: EMBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…In a European setting, Mackenbach et al . reported that both social cohesion and social network were associated with lower odds of being obese (not so clear in the case of overweight) . Cohen et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In a European setting, Mackenbach et al . reported that both social cohesion and social network were associated with lower odds of being obese (not so clear in the case of overweight) . Cohen et al .…”
Section: Resultsmentioning
confidence: 97%
“…This is, to our knowledge, the first systematic review on social capital and obesity conducted from a social capital theory perspective. In 2016, Glonti et al published in this journal a systematic review on the psychosocial determinants of obesity, which included studies that reported a relationship between adult weight status and five psychosocial environmental constructs: collective efficacy, social cohesion, social capital and social support (45). From a social capital theory approach, as described in the introduction of this paper, all these constructs comprise different dimensions of social capital and, in fact, some of the papers reviewed by Glonti (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Explanations of the perceived effect of social networks include social contagion (whereby the network influences obesity-related behaviours via modelling), social capital (whereby a sense of belonging and social support influence obesity-related behaviours) and social selection (whereby an individual's network is a function of their weight) [29]. In a recent systematic review, we showed that the strongest social environmental correlates of obesity were, indeed, social capital and collective efficacy, but, in general, few social environmental factors were consistently related to adult obesity [30]. …”
Section: Identifying Upstream Determinants Of Obesitymentioning
confidence: 99%
“…Moreover, the European context provided a valuable added dimension as a result of both the differences between the countries in which the research took place and their similarities. The systematic reviews on the built and social environment demonstrated the heterogeneity within the existing literature. A systematic review of virtual audit tools demonstrated the feasibility and reliability of using this novel approach for assessing the built environment .…”
mentioning
confidence: 99%